Development of hard skills and soft skills towards BUMDES performance profesionalism in Bintan District - Nurhasanah, Nurhasanah; Wulandari, Kiki (Journal of Economics and Business Letters, 2023)
This study aims to determine the partial, simultaneous influence, and the direct and indirect effects of the development of hard skills and soft skills on the professionalism of BUMDes performance in Bintan. This research is categorized as quantitative research because it uses a questionnaire as a research instrument, which is primary data in this study. The population in this study is all BUMDes managers in Bintan Anculai. The sampling technique used is non-probability sampling, and a saturated sample is used to determine the sample